Factors associated with cerebral edema in children under 5 years of age admitted in an intensive care unit and their outcome. (September 2019) - Islam, Shamin; Sarmin, Monira; Ahmed, Tahmeed; Afroze, Farzana; Chisti, Mohammod Jobayer
Objective: We aimed to evaluate risk factors and outcome of cerebral edema in children with diarrhea. Methods: In this retrospective chart analysis, data of all diarrheal children under 5 years of age having convulsion and admitted in intensive care unit were retrieved from an electronic medical record system of Dhaka Hospital of International Centre for Diarrhoeal Disease Research, Bangladesh, from 1st January 2011 to 31st December 2016. Comparison of clinical and laboratory characteristics was made between children with (cases = 22) and without cerebral edema (controls = 66). Results: Cases more often had a fatal outcome than controls (36% vs 8%, p = 0.003). In logistic regression analysis, after adjusting for potential confounders, the cases were independently associated with respiratory distress (odds ratio = 5.5, confidence interval = 1.55–19.62, p = 0.008), severe sepsis (odds ratio = 4.6, confidence interval = 1.24–16.77, p = 0.022), and severe malnutrition (odds ratio = 0.16, confidence interval = 0.04–0.74, p = 0.019). A rapid drop (>0.5 mmol/L per hour) in serum sodium did not have any impact on developing cerebral edema (p = 0.090). Conclusion: Identification of simple clinical predictors may help in the early treatment of cerebral edema that may further help in reducing deaths in such children especially in resource-poor settings. However, further research with prospective design is needed to consolidate our observation.